2017
DOI: 10.3390/ijms18051046
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Genes Regulated by AtWRKY6 Using Comparative Transcript and Proteomic Analysis under Phosphorus Deficiency

Abstract: Phosphorus (P) is an important mineral nutrient for plant growth and development. Overexpressing AtWRKY6 (35S:WRKY6-9) was more sensitive and wrky6 (wrky6-1) was more resistant under low Pi conditions. To better understand the function of AtWRKY6 under low phosphate stress conditions, we applied two-dimensional gel electrophoresis (2-DE) to analyse differentially expressed proteins in the shoots and roots between wild type, 35S:WRKY6-9 and wrky6-1 after phosphorus deficiency treatment for three days. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Based on this, it was indicated that changes in expression of these target proteins could represent a signi cant effect of biological treatment on samples. Using these data, we selected proteins with ≥ 1.5-fold changes as an additional standard (refer to [19]) and the volcano pot was drawn by using two factors of protein expression fold changes and p value obtained from t test to show the signi cant differential protein accumulation between RLP and RCK (Figure 1e). The results showed that 60 protein groups were up-regulated (Table 1) and 15 down-regulated (Table 2).…”
Section: Label-free Quantitative Proteomic Analysismentioning
confidence: 99%
“…Based on this, it was indicated that changes in expression of these target proteins could represent a signi cant effect of biological treatment on samples. Using these data, we selected proteins with ≥ 1.5-fold changes as an additional standard (refer to [19]) and the volcano pot was drawn by using two factors of protein expression fold changes and p value obtained from t test to show the signi cant differential protein accumulation between RLP and RCK (Figure 1e). The results showed that 60 protein groups were up-regulated (Table 1) and 15 down-regulated (Table 2).…”
Section: Label-free Quantitative Proteomic Analysismentioning
confidence: 99%
“…The artificial breeding and restoration of F. mandschurica is urgently needed. Phosphorus (P) is one of the most important elements involved in the growth and development of plants (Li et al, 2017). Although the total amount of P in soil is abundant, P is easily fixed by minerals and organic matter (Fink et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, transcription factors associated with the bZIP family (e.g., ABI5 and TGA1) were only detected in cluster 5. The presence of WRKY6 in this cluster suggests its involvement in phosphate transport and assimilation (Li et al., 2017), which can be important to seed filling/maturation. Clusters 1 and 4 were characterized by a considerable downregulation at 15 DAF and a slightly change by 18 DAF for d2hgdh1‐2 (42 and 94 transcripts, respectively).…”
Section: Resultsmentioning
confidence: 99%